THE EFFECT OF METACOGNIFY MODEL ON EXPOSITION TEXT LEARNING IN CLASS VIII ISLAMIC HIGH SCHOOL ATHIRAH MAKASSAR - Lulu Isnaeni; Aswati Asri; Muhammad Saleh (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine the effect of metacognitive learning models in exposition text learning in class VIII SMP Islam Athirah Bukit Baruga Makassar with reference to student learning outcomes and student activities. The research method used is pre-experimental research involving one group that is given treatment. The population of this study were all eighth grade students of SMP Islam Athirah Bukit Baruga Makassar in the odd semester of the 2021/2022 academic year. The sample was chosen randomly so that a sample of 78 students was obtained. Data collection was carried out using learning outcomes tests (pretest and posttest) and student activity observation sheets. The data analysis technique used is descriptive and inferential statistical analysis. The results of descriptive and inferential statistical analysis showed: (1) The average score (pretest) was 67.92 in the low category while (posttest) was 91.10 in the very high category, (2) The average percentage of student activity reached 92%, which means Student activity is categorized as very influential (3) the t-test value shows ttable = 1.708 and tcount = 34.18 p = 0.000 which means significant, (4) The gain score = 23.18 means that there is an increase in value. It can be concluded that the metacognitive learning model has an effect on student learning outcomes in text-based Indonesian language learning with the subject matter of exposition texts in class VIII of SMP Islam Athirah Bukit Baruga Makassar.